(untitled) (KULT_online, 2012)
Stefanie Hirsbrunner’s analysis pursues a political science objective and not, as one might think from the title, a film studies one. By using a descriptive-analytical comparison, she examines the ’White Hero’ of five selected Hollywood blockbusters. This is put into practice with postcolonial concepts as well as the examination of inherent racism in the American filmmaking industry closely related to the hero ideal. Hollywood’s treatment of ’race’ and the intention of the respective filmmakers are in the focus of this analysis, as well as the staging of the White Hero and his interaction with non-whites. Although Hirsbrunner succeeds in carving out a trend toward reproducing colonial paradigms, she isn’t able to prove that this happens intentionally and because of profit motives.